Deciphering emoji variation in courts: a social semiotic perspective - Jiamin Pei; Le Cheng (Humanities & Social Sciences Communications, 2022)
Abstract Emojis are increasingly being used as digital evidence in courts due to the miscommunication and misinterpretation arising from the high variability of their usage and interpretation. Emojis in courts have been extensively researched in extant studies, but relatively little attention has been paid to the emoji variation phenomena in Chinese courts. Through an empirical qualitative content analysis of the court judgments in China and the United States and some supplementary materials, this study posits that an emoji’s meaning in courts can be subject to the following six categories of variations: i. variation across platforms, including devices, operating systems, software programs and clients; ii. temporal variation; iii. variation in court cases under different rules of evidence; iv. variation in individual participants; v. variation across social groups; and vi. linguistic-cultural variation. From a social semiotic perspective, emojis as dynamic signs have great meaning potentials, making their meanings context-dependent and interpreter-dependent. For this reason, it is suggested that legal professionals untangle and weave historical, social, cultural and legal contexts into the interpretation of an emoji’s meaning. Moreover, a probe into the contextualized configuration of emojis can offer practical insights into the interpretation of emoji-bearing texts in judicial decision-making as well as the admissibility and investigation of digital evidence in courts.